Cross-Theoretical Compliance: An Integrative Compliance Analysis of COVID-19 Mitigation Responses in Israel. Issue 4 (April 2023) - de Bruijn, Anne Leonore; Feldman, Yuval; Reinders Folmer, Christopher P.; Kuiper, Malouke E.; Brownlee, Megan; Kooistra, Emmeke; Olthuis, Elke; Fine, Adam; van Rooij, Benjamin
To understand the question why people obey or break rules, different approaches have focused on different theories and subsets of variables. The present research develops a cross-theoretical approach that integrates these perspectives. We apply this in a survey of compliance with COVID-19 pandemic mitigation rules in Israel. The data reveal that compliance in this setting was shaped by a combination of variables originating from legitimacy, capacity, and opportunity theories (but not rational choice or social theories). This demonstrates the importance of moving beyond narrow theoretical perspectives of compliance, to a cross-theoretical understanding—in which different theoretical approaches are systematically integrated.